(untitled) (Global Media Journal - German Edition, 2018)
Research on European integration posits that people support and identify with the European Union (EU) by considering its economic benefits. Thus, it is argued that people’s sense of identity and their degree of political support for the EU can be explained by estimating the economic prosperity it yields. However, the current paper illustrates that in addition to utilitarian factors, media use can also explain political support for the EU. Thus, to examine this relationship between political support and the media, the study uses the political support framework by David Easton along with the theoretical underpinnings of the media malaise and media mobilization effects. The empirical analysis is conducted on the basis of secondary data obtained through Eurobarometer surveys. Furthermore, to test if the economic factors are a strong predictor of political support, the study assumes that the recent Eurozone crisis has caused a sharp decline in political support. Therefore, it investigates the role of different economic factors and media on political support before and after the crisis. The results indicate that consuming information from the television (TV) does not lead to malaise but rather, that it has a mobilization effect. Furthermore, the results reveal that the respondents’ informedness and their TV usage for getting information predict political support better than the economic indicators.